The consumption of popular culture products among Japanese language learners at Universiti Teknologi Mara - Ahmad, Normah; Mamat, Roslina (Human Resource Management Academic Research Society, 2022)
Today, Japanese popular culture stands as one of the leading and most prominent popular cultures around the world. Many researchers from the West studied Japanese popular culture and its relation to various aspects, namely teaching and learning Japanese, tourism, product selling, and also cultural exchange between Japan and the rest of the world. The current study aims to investigate the consumption of Japanese popular culture products among the Japanese language learners at Universiti Teknologi MARA (UiTM). The result from the study indicates that the consumption of Japanese popular culture products is high among Japanese as a Foreign Language (JFL) learners, and this could be implied that they are very interested in anime, manga, song, and seiyu (voice actor), and these are used as a tool to improve their proficiency in the Japanese language.